COVID-19-A CHALLENGE FOR THE HEALTHCARE SYSTEM - Wazir, Sana (Journal of Gandhara Medical and Dental Science, 2021)
Until the last century, coronavirus have been associated with non-severe respiratory infections in humans’. In December 2019, a new coronavirus was isolated in patients related to the Wet market in the city of Wuhan (China)². It rapidly spread across the world and has become the largest pandemic since the Spanish Flu in 1918. More than half a million people worldwide were infected by the end of March 2020 with an increasing number of deaths being reported³ The first COVID-19 case in Pakistan was reported in the end of February, since than the total confirmed cases of COVID- 19 are 261,914 and reported deaths of 5,522 and recovered cases are 198,509⁴. By now we are all aware of the symptoms of the still evolving disease, which can include cough, fever and chills, muscle pain, sore throat, shortness of breath and loss of taste and smell. It can also include gastrointestinal symptoms and headaches. The year 2020 has proved to be a nightmare for the economy and health care; creating a panic situation across the world⁵. It is a three-fold challenge for the health care professionals: one concerning health care of the general population and prevention and control of infection in the community, secondly providing health care facilities for combating this critical situation, and thirdly safety and protection of the front-liners³. This is an uphill task for developing countries like Pakistan due to low socioeconomic reasons⁵. The virus is transmitted from human to human droplets putting the medical personnel at greater risk and requiring the use of full personal protective equipment (PPE) as they are in close contact with such patients. The shortage of PPE is a worldwide problem. Proper triage systems should be established at different health care centers for screening of suspected COVID-19 patients. Infected patients require critical care and assisted ventilation which needs professional training of staff who are involved in care of virus infected patients. High demand for ventilators and establishment of high dependency units on emergency basis is also a challenge. The emerging need for experienced frontline health care professionals is putting our skeletal health care system under a lot of pressure. As we are eagerly waiting for drugs and vaccines to combat this pandemic, the only option we have is to take precautions. However, health care professionals cannot stay away from the patients nor can they avoid contact with suspected cases of COVID-19. They are the frontline warriors fighting with full strength. They are under tremendous physical and mental stress. Many doctors across the world have lost their lives mainly in China and Italy, and several deaths have been reported in Pakistan. Apart from their health, they are at a high risk of transmitting the disease to family and friends. Many queries still need to be answered in research for best scientific evidence in order to prevent and control spread of COVID-19 and clinical management of infected patients. COVID-19 pandemic is a challenge for health care system globally, which should be combated with improvement in acquiring knowledge about the disease, spreading that knowledge to the common man and getting acclimatized with the new normal by changing our practice guidelines for providing best medical care. Public awareness and strict adherence to standard operational procedures cannot be stressed enough to control the spread of the novel coronavirus.